2010
DOI: 10.4028/www.scientific.net/amr.126-128.195
|View full text |Cite
|
Sign up to set email alerts
|

Tool Wear Mechanism in Continuous Cutting of Difficult-to-Cut Material under Dry Machining

Abstract: Wear mechanism on the flank of a cutting tool is caused by friction between newly machined surface and the cutting tool, which plays predominant role in determining tool life. Detailed study on wear mechanism at the cutting edge of carbide tools were carried out at cutting speed of 55 – 95 m/min, feed rate of 0.15 – 0.35 mm/rev and depth of cut of 0.10 – 0.20 mm. The wear on the cutting tools was occurred predominantly on the nose radius, as effect of lower feedrate and nose radius selected. Various wear obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“…As stated by previous researcher that nose radius and feed rate have a significant correlation to surface texture of new machined surface when machining super alloy materials [10]. Meanwhile, Gusri, et.al [9] found that when machining super alloy material, surface texture of machined surface formed were affected by worm tool. …”
Section: Feed Marks On the Machined Surface Of Magnesium Alloy After mentioning
confidence: 76%
See 1 more Smart Citation
“…As stated by previous researcher that nose radius and feed rate have a significant correlation to surface texture of new machined surface when machining super alloy materials [10]. Meanwhile, Gusri, et.al [9] found that when machining super alloy material, surface texture of machined surface formed were affected by worm tool. …”
Section: Feed Marks On the Machined Surface Of Magnesium Alloy After mentioning
confidence: 76%
“…The feed rate directly effect on feed mark at the machined surface. Beside of the feed rate, wear on the tool surface also contribute on the feed mark on the new machined surface [9]. …”
Section: Effect Of Rotary Tool Speed On the Surface Roughness Valuesmentioning
confidence: 99%
“…Rata-rata pemesinan basah (wet machining) masih banyak digunakan pada industry otomotif (Tonshoff, et.al, 1997) [2]. Pemesinan basah adalah sejumlah cairan dialirkan ke kawasan pemotongan bertujuan untuk menurunkan suhu pemotongan dan melumasi bagian-bagian pemesinan sehingga diharapkan permukaan pemesinan memiliki integritas permukaan yang dapat meningkatkan masa pakai alat potong (life time) [3,4].…”
Section: Pendahuluanunclassified
“…Pada proses pemotongan berlangsung sisi potong alat potong dan benda kerja saling berinteraksi sehingga terjadi kenaikan temperatur pemotongan [3,4]. Walaupun temperatur pemotongan sebesar 80% terbawa oleh tatal/geram yang mengalir namun akibat alat potong dan benda kerja terus bersinggungan/bergesekan maka sisi alat potong akan menjadi panas dan mengalami abrasi [5].…”
Section: Pendahuluanunclassified
“…Kinerja lapisan berbahan Titanium Nitrida (TiN) yang terdapat pada alat potong tidak sesuai dengan fungsinya bilamana memotong paduan Titanium Ti-6246 pada operasi milling kecepatan potong (Vc) 55 m/menit, gerak makan (f) 0,1 mm/gigi dan kedalaman pemakanan (a) 2 mm didapati lapisan mengalami pengelupasan di awal proses pemotongan (initial wear) dan disimpulkan sebagai akibat dari reaktifitas yang tinggi pada Titanium Ti-6246 selama proses pemotongan berlangsung [6]. Temuan lain yang berkaitan dengan pengelupasan pelapis terhadap bahan dasar alat potong di awal pemotongan juga pada bahan paduan Titanium dengan operasi bubut dengan kecepatan potong (Vc) 55 m/menit, gerak makan (f) 0,15 mm/put dan kedalaman potong (a) 0,10 mm [2].…”
Section: Latar Belakangunclassified